Analysis of Genetic Diversity of 45 Guava Germplasm Evaluated Using SSR Markers. Issue 3 (2nd July 2020) - Ma, Zehua; Liu, Shunzhi; Liang, Ziwei; Xu, Shejin; Hu, Weirong
ABSTRACT: The genetic relationships of 45 individuals of Psidium guajava from six cultivars were analyzed by screening SSR primers with high polymorphism and good repeatability, which provided a scientific basis for the collection, protection, and utilization of guava germplasm resources in China. In this study, we analyzed genetic diversity and cluster of 45 guava materials using 15 pairs of polymorphic SSR primers. The number of polymorphic bands was 65 with the polymorphism ratio of 97.01%, and the molecular weight of the band ranges from 102 bp to 500 bp. Only two polymorphic bands were detected by primer mPgCIR23, which was the least. In contrast, primer mPgCIR08 detected seven bands with the highest number of polymorphic bands. The average polymorphism information content of the markers was 0.60, Nei's genetic diversity was 0.29, and Shannon's index was 0.44. Additionally, the variation range of genetic similarity coefficient was 0.37–0.99. The clustering pattern generated from the UPGMA method distinctly grouped the cultivated varieties and the seedling strain into four groups when the genetic similarity coefficient is 0.68. All the seedling strains (except S9) were successfully clustered into three subgroups, which confirmed that they were progenies from three different guava varieties, respectively.